Computational topology in image context : 7th International Workshop, CTIC 2019, Málaga, Spain, January 24-25, 2019, Proceedings /: 7th International Workshop, CTIC 2019, Málaga, Spain, January 24-25, 2019, Proceedings. (2019) - Unknown
No abstract available